Zinc Industry - Hewitt, Ken.; Wall, Tony.; Hewitt, Ken.; ScienceDirect eBooks (Cambridge : Woodhead Pub., 2000)
This looseleaf industry handbook provides a comprehensive and practical guide to the workings of the international zinc industry. Concise and lucid, it considers trading techniques and strategies for different market users and includes useful appendices on zinc specifications and the world's major zinc and lead mines. It is essential for all those involved in the industry. A comprehensive guide to the workings of the international zinc industryWritten by well known industry insidersExamines future trends in demand, trade and pricing.
Part 1. Origins and production -- part 2. Properties and applications -- part 3. The market -- part 4. The future outlook -- part 5. Appendices.
Originally published as: The international zinc trade by Ken Hewitt and Keith Patten.
Title from content provider.
Elsevier
Keywords: Zinc industry and trade; BUSINESS & ECONOMICS -- Industries -- General; Zinc industry and trade; Electronic books